Model of cooperatives contribution to the sustainable and rural development - Arsenijević, Jasmina; M. Nikolić, Marija (Economics of Agriculture, 2010)
In this paper is presented the model of support to rural and sustainable development based on expanding role of agricultural cooperatives on education, promotion and support through straightening multifunctional agriculture. Idea is that agricultural cooperatives that already have some educational role activate in informal education of rural population, straightening their awareness of sustainable development problems and their role in preventing and direct blocking of environment pollution in work and life in villages. Beside promotion of pure technologies, organic production, use of alternative source of energy or waste recycling; rural population would be introduced to new developing possibilities of village tourism, national handicraft industry, folklore and other rural potentials thorough different models of informal education.